Innovative human capital management of energy enterprises and the role of shaping the environmental behavior of consumers of green energy based on the work of smart grids - Liakhovych, Galyna (2021)
The use of Internet of Things programs in various fields of activity testifies the reset of the human lifestyle. Climate change and limited access to natural resources are factors for shaping the environmental behavior of energy consumers. Ensuring the development of Smart specialization and innovation in the energy sector provides the transformation of a set of competencies and skills, the organization of the workspace based on digitalization, as well as the increasing role of continuous personnel training at energy enterprises. Considering this, the article is devoted to the development of a system of innovative human capital management of energy enterprises in the context of environmental behavior formation of consumers of green energy based on the work of Smart Grids, the solution of the issue of identification and the formation of appropriate digital competencies to optimize the process of marketing promotion of green energy services in the virtual space. For this, the role of human capital formation in the innovative development of an energy enterprise and the approval of the foundations for organizing a virtual socio-economic space based on the work of smart grids.The relationship between the formation of environmental behavior of consumers of green energy and the need to develop digital competencies of employees of energy enterprises has been proved. The level of the use of innovative technologies for the development of personnel in the field of energy has been investigated and a set of digital competencies necessary for the development of the industry in the conditions of the formation of environmental behavior of consumers of green energy based on the operation of Smart Grids has been established. The analysis of the dynamics of the use of computers, computer networks, and social media at Ukrainian enterprises by types of economic activity indicates an increase in the level of use of social media and mobile networks. The algorithm for managing the human capital of energy enterprises in the virtual space has been optimized for the formation of digital competencies based on the work of Smart Grids, which will contribute to ensuring the transition to an increase in the consumption of green energy.